2019
DOI: 10.1016/j.nuclphysa.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of spin induced structural transitions on level density and neutron emission spectra

Abstract: The impact of spin induced deformation and shape phase transitions on nuclear level density and consequently on neutron emission spectra of the decay of compound nuclear systems 112 Ru to 123 Cs (N = 68 isotones) is investigated in a microscopic framework of Statistical theory of superfluid nuclei. Our calculations are in good accord with experimental data for evaporation residue of 119 Sb and 185 Re and show a strong correlation between spin induced structural transitions and NLD. We find that the inverse lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In contrast to the strong dependence of the LD parameter on the angular momentum reported in the above mentioned works, experimental data for the heavier systems showed less sensitivity of k on J [35,36]. Some of the experimental data on the angular dependence of k could be successfully explained by the theoretical calculations by considering spin induced deformation and shape phase transitions under the framework of a statistical theory of hot rotating nuclei [41,42]. In view of the observed variation of the level density parameter with J in the earlier works, it will be interesting to extend the study for similar systems especially to higher spin regions.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…In contrast to the strong dependence of the LD parameter on the angular momentum reported in the above mentioned works, experimental data for the heavier systems showed less sensitivity of k on J [35,36]. Some of the experimental data on the angular dependence of k could be successfully explained by the theoretical calculations by considering spin induced deformation and shape phase transitions under the framework of a statistical theory of hot rotating nuclei [41,42]. In view of the observed variation of the level density parameter with J in the earlier works, it will be interesting to extend the study for similar systems especially to higher spin regions.…”
Section: Introductionmentioning
confidence: 66%
“…It is observed that the experimental k-values increases as a function of the mean angular momentum for both the 16 O + 93 Nb and 20 Ne + 93 Nb reactions in the measured angular momentum range of <J>≈ 20 -36 . The experimental results have been compared with the microscopic calculations performed using the statistical model of hot rotating nuclei [41,42,62], described briefly in the following section (Sec. III C).…”
Section: B Angular Momentum Dependence Of Kmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental techniques such as the measurement of primary γ−ray spectra [17], direct counting of nuclear levels [18][19][20][21], analysis of neutron resonance spacings [22], and SM analysis of particle-evaporation spectra in Heavy-Ion fusion reactions [23][24][25][26][27][28][29][30][31][32][33][34][35][36] to compute the nuclear level density provide useful information on various aspects of statistical behaviour of compound nuclei and level densities. Comparison of the spacings of nuclear levels in the neutron resonance data for closed shell and mid-shell nuclei at a similar excitation energy reveal [37][38][39][40] that the larger shell gap in magic nuclei results in much smaller density of resonances pointing towards a strong dependence of level density on nuclear shell structure [41][42][43][44][45]. The nuclear shell effects [46][47][48], that arise from one-body interactions, are known to provide extra stability to the closed shell magic nuclei that seem to play a major role in the nuclear phenomena like production of super heavy elements (SHE) [49,50], fission isomers [51], superdeformed nuclei [52] and changing magicity in exotic nuclei [53][54][55].…”
Section: Introductionmentioning
confidence: 98%